KEKUATAN MENDONGENG DALAM PERWUJUDAN PERILAKU BERBAHASA ANAK USIA PRASEKOLAH - Tressyalina Tressyalina (JURNAL PENDIDIKAN ROKANIA, 2016)
This research aims to describe the power of storytelling in the embodiment of language behavior of preschoolers. This is due to storytelling is very important for children's language perkambangan. In addition, through storytelling, preschoolers can provide various forms of verbal and nonverbal responses typical as an expression of language behavior, both at the time before the fairy tale is told, when told, and after told. However, this would depend on the success story presenter as a storyteller in selecting and applying models storytelling performance. Thus, the power of storytelling in the embodiment of language behavior of preschool children are important to understand